FRI0480 Thiol/disulphide Homeostasis in Familial Mediterranean Fever. (15th July 2016) - Doğru, A.; Balkarlı, A.; Cetin, G.Y.; Neselioglu, S.; Erel, O.; Sahin, M.; Tunc, S.E.
Abstract : Background: Familial Mediterranean fever (FMF) is an autoinflammatory disease that include recurrent episodes of peritonitis, pleuritis, and arthritis, with accompanying fever. FMF is caused by mutations in MEFV and typically diagnosed during childhood. Thiol/disulphide homeostasis, marker of oxidative stress, is associated with an increased in inflammatory cytokines in many inflammatory diseases. Objectives: We aimed to investigate the dynamic thiol/disulphide homeostasis in patients with FMF during attact free period. Methods: Fifty five patients with FMF during attact free period, 55 patients with Ankylosing Spondylitis (AS) during inactive period and 55 age-and sex matched controls were included in the study. Native thiol, total thiol and disulphide levels were studied by the Erel and Neşelioğlu method. Results: Total thiol and disulphide levels were significantly lower in FMF group compared to healthy controls. Native thiol levels were detected to be significantly increased in FMF groups compare to AS group. However, total thiol levels were similar in FMF and AS group. Ratios obtained using plasma native thiol, total thiol, and disulphide levels differed significantly between the FMF, AS and the control group. Conclusions: Thiol levels, an important anti-oxidant, was found to be significantly lower. Subclinical inflamation may be continued in FMF patients during attact free period. Randomised controlled trials with large patient populations might help clarify this issue. Disclosure of Interest: None declared